Implementation Implementation of Business Education and Digital Marketing Literacy to Improve Technopreneurship Competence in influencing strategies to maintain SMEs in the Pandemic Era - maula, farij ibadil; Saraswati, Thusy Tiara; Wibowo, Nyu Herno Aris; Harwida, Gleydis (Jurnal Entrepreneur dan Entrepreneurship, 2021)
The current pandemic condition, SME players must be able to adapt and expand their business strategy from conventional ones to digital ones, such as Facebookads, Instagram Business, Shopee, Lazada, OLX, Bukalapak, etc. The purpose of this research is to conduct a comprehensive study on the implementation of business education and digital marketing literacy to improve Technopreneurship competencies in influencing strategies to maintain SMEs in the Pandemic Era. This research was conducted using descriptive qualitative methods by means of observation, documentation and interviews. Seen from the point of view of the place of research, this research is included in the type of field research multisite field research. The application of Business Education and digital marketing literacy is able to arouse entrepreneurial, independent and creative enthusiasm. The application of Business Education has been considered as one of the important factors to foster and develop entrepreneurial passion, spirit and behavior among SMEs. Business education can shape the mindset, attitude, and behavior of being a true entrepreneur, thereby directing them to choose entrepreneurship as a career choice. Digital marketing literacy is very effective in increasing competence Technopreneurship can be used as a survival strategy in the era of the Covid pandemic. The sophistication of digitalization serves as a means of carrying out promotional activities, so it is easy to exchange information with anyone through existing facilities.